THE VOICE OF FREEDOM IN BOB MARLEY’S SONG LYRICS - BEATRICE, ADELINE (Jurnal Ilmiah Mahasiswa FIB, 2014)
Beatrice Adeline. 2013. The Voice of Freedom in Bob Marley’s Song Lyrics. Study Program of English, Department of Languages and Literature, Faculty of Cultural Studies, Universitas Brawijaya. Supervisor: Juliati; Co-supervisor: Aris Siswanti.  Keywords: Bob Marley, voice of freedom, song lyrics, the kinds of freedom Song lyrics can express the social condition of the society. Song lyrics can also be used to deliver messages of freedom and peace. Some of the song lyrics that reflect the social condition are Bob Marley’s songs. Bob Marley is a well known Jamaican singer. Bob Marley’s song lyrics entitled Blackman Redemption, Rebel Music, Redemption Song, Smile Jamaica and Slave Driver reflect the voice of freedom. These songs reflect what happens to Jamaican people who used to be colonized by Spain and British.  The research employs sociological approach as the grounding theory to analyze the voice of freedom which is reflected in each song based on the kinds of freedom such as self freedom, collective freedom, spiritual freedom, and political freedom. The biography of Bob Marley and references about social condition in Jamaica are used as supporting information for the analysis.  The result of this study shows that Bob Marley’s song lyrics express the four kinds of freedom.  Self freedom is the first dominant theme. The  second is spiritual freedom,  and the  third is collective freedom, and the last is political freedom. Through  his songs, Bob Marley spreads the messages of freedom and peace by referring to the Jamaican’s experience in the colonial era. It is suggested that further researchers use semiotic approaches in Bob Marley’s other songs because many of his songs use symbols related to the Jamaican culture as the Rastafarians.